2013
DOI: 10.1016/j.jacc.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of a Pediatric Cohort With Short QT Syndrome

Abstract: SQTS is associated with aborted sudden cardiac death among the pediatric population. Asymptomatic patients with a Gollob score of <5 remained event free, except for an isolated episode of supraventricular tachycardia, over an average 6-year follow-up. A higher modified Gollob score of 5 or more was associated with the likelihood of clinical events. Young SQTS patients have a high rate of inappropriate ICD shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…46 Sixteen patients (84%) had a familial or personal history of cardiac arrest. A gene mutation associated with short-QT syndrome was identified in 5 of 21 probands (24%).…”
Section: Sudden Cardiac Arrestmentioning
confidence: 99%
“…46 Sixteen patients (84%) had a familial or personal history of cardiac arrest. A gene mutation associated with short-QT syndrome was identified in 5 of 21 probands (24%).…”
Section: Sudden Cardiac Arrestmentioning
confidence: 99%
“…These findings may reflect similar manifestations of aberrations in atrial refractoriness. Villafañe et al 19 found that 24% with short-QT syndrome experienced aborted sudden cardiac death during follow-up. In our study, no patients were documented to have experienced aborted sudden cardiac death or ventricular arrhythmia during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Giustetto et al [6], 3 children with SQTS presented with aborted sudden cardiac death or syncope during infancy and 2 other neonates in families with SQTS had died suddenly. Villafañe et al [15] reported symptoms in 14 (56%) of 25 SQTS pediatric patients, including aborted sudden cardiac death in 6 (24%). Arrhythmias included ventricular fibrillation in 6 and AF in 4 patients of the pediatric cohort.…”
Section: Discussionmentioning
confidence: 99%